Morphological and simple sequence repeat (SSR)-based diversity of Capsicum germplasm characterizes population structure and enables marker-assisted selection for Phytophthora capsici resistance - Deepa Jaganathan; Jessica Michelle Gibbs; Noel Thomas; Theodore McAvoy; Mahnaz Azad; Miaoying Tian; Dennis N. Lozada; William Hendricks Railey; Amol N. Nankar (Euphytica, 2026)
Capsicum annuum is a globally important crop with rich genetic diversity that underpins breeding for productivity and disease resistance. In this study, we assessed 485 accessions representing a diverse Capsicum germplasm set, predominantly Capsicum annuum with a limited representation of related wild species using agro-morphological traits and simple sequence repeat markers to explore diversity, structure, and trait variation. Phenotypic evaluation of 352 accessions was conducted under field conditions during the 2024 summer season, where data were recorded on eight quantitative and four qualitative traits. Genetic characterization on the whole collection was performed using 24 polymorphic SSR markers selected for their known linkage to Phytophthora capsici resistance. A total of 308 alleles were detected post-binning, with an average of 12.83 alleles per locus and high polymorphism information content (mean PIC = 0.80). STRUCTURE analysis revealed three major genetic clusters (K = 3), supported by the Evanno ΔK method and consistent with clustering observed in Principal Component Analysis (PCA) and Neighbor-Joining (NJ). The clusters comprised predominantly C. annuum accessions, but also included individuals from C. baccatum , C. chinense , and other species, suggesting historical introgression and admixture. Phenotypic variation largely aligned with molecular groupings, supporting the complementary use of morphological and marker-based data. The high allelic diversity and defined population structure observed in this study provide a valuable foundation for genetic improvement, association mapping, and core collection development in Capsicum . In addition, the choice of Phytophthora -linked SSR markers provides an important platform for future association mapping and marker-assisted selection studies aimed at improving disease resistance in Capsicum . Graphical Abstract

Unique humoral immune response of pigs to repeated natural Japanese encephalitis virus infections: an amplifying host perspective - M. Dhanalakshmi; Himani Dhanze; Akash Mote; N. Narmatha; K. Sibi Thomas; R. Nithiaselvi; Deepa Mehta; M. Suman Kumar; K. N. Bhilegaonkar (Archives of Virology, 2025)

Sequential Profiling of Anti-SARS CoV-2 IgG Antibody in Post COVID-19 Patients - Ajaikumar Sukumaran; Rhema Elizabeth Thomas; R. Arun Krishnan; Thushara Thomas; Riji Thomas; Deepa K. Vijayan; Jofy. K. Paul; D. M. Vasudevan (Indian Journal of Clinical Biochemistry, 2022)

Automated grading of diabetic retinopathy using CNN with hierarchical clustering of image patches by siamese network - V. Deepa; C. Sathish Kumar; Thomas Cherian (Physical and Engineering Sciences in Medicine, 2022)

Inferring ecological strategies of Psenopsis spp. (Teleostei: Centrolophidae) inhabiting Indian waters from morphological features - K. V. Aneesh Kumar; M. P. Rajeeshkumar; M. Hashim; K. P. Deepa; J. L. Otero-Ferrer; N. Saravanane; Sujitha Thomas; K. K. Bineesh; V. M. Tuset (Marine Biology Research, 2022)

High-frequency direct shoot induction from leaf explants of Pogostemon quadrifolius (Benth.) F. Muell.: an ethnomedicinal herb - A. V. Deepa; T. Dennis Thomas (In Vitro Cellular & Developmental Biology - Plant, 2022)

Retrieval of Broadband Optical Properties from Ambient Aerosols Measurements Using Inverse Mie Calculations - Aiswarya Saseendran; Shebin John; Anoop Pakkattil; Arun P. Thomas; Sushmitha Adiga; Jun Chen; Claudio Mazzoleni; Deepa Viswanath; Ravi Varma (Aerosol Science and Engineering, 2022)

Single-Turnover Variable Chlorophyll Fluorescence as a Tool for Assessing Phytoplankton Photosynthesis and Primary Productivity: Opportunities, Caveats and Recommendations - Nina Schuback; Philippe D. Tortell; Ilana Berman-Frank; Douglas A. Campbell; Aurea Ciotti; Emilie Courtecuisse; Zachary K. Erickson; Tetsuichi Fujiki; Kimberly Halsey; Anna E. Hickman; Yannick Huot; Maxime Y. Gorbunov; et al. (Frontiers in Marine Science, 2021)
Phytoplankton photosynthetic physiology can be investigated through single-turnover variable chlorophyll fluorescence (ST-ChlF) approaches, which carry unique potential to autonomously collect data at high spatial and temporal resolution. Over the past decades, significant progress has been made in the development and application of ST-ChlF methods in aquatic ecosystems, and in the interpretation of the resulting observations. At the same time, however, an increasing number of sensor types, sampling protocols, and data processing algorithms have created confusion and uncertainty among potential users, with a growing divergence of practice among different research groups. In this review, we assist the existing and upcoming user community by providing an overview of current approaches and consensus recommendations for the use of ST-ChlF measurements to examine in-situ phytoplankton productivity and photo-physiology. We argue that a consistency of practice and adherence to basic operational and quality control standards is critical to ensuring data inter-comparability. Large datasets of inter-comparable and globally coherent ST-ChlF observations hold the potential to reveal large-scale patterns and trends in phytoplankton photo-physiology, photosynthetic rates and bottom-up controls on primary productivity. As such, they hold great potential to provide invaluable physiological observations on the scales relevant for the development and validation of ecosystem models and remote sensing algorithms.

Bioplastic production from renewable lignocellulosic feedstocks: a review - R. Reshmy; Deepa Thomas; Eapen Philip; Sherely A. Paul; Aravind Madhavan; Raveendran Sindhu; Ranjna Sirohi; Sunita Varjani; Arivalagan Pugazhendhi; Ashok Pandey; Parameswaran Binod (Reviews in Environmental Science and Bio/Technology, 2021)

In vitro strategies for the conservation of Indian medicinal climbers - A. V. Deepa; T. Dennis Thomas (In Vitro Cellular & Developmental Biology - Plant, 2020)

A parasporin from Bacillus thuringiensis native to Peninsular India induces apoptosis in cancer cells through intrinsic pathway - Thomas Chubicka; Devaki Girija; Kizhakkeettil Deepa; Sasidharan Salini; Nair Meera; Achuthan Chathrattil Raghavamenon; Menon Kunnathully Divya; Thekkekara Devassy Babu (Journal of Biosciences, 2018)

Accumulation of mercury and other heavy metals in edible fishes of Cochin backwaters, Southwest India - Mahesh Mohan; M. Deepa; E. V. Ramasamy; A. P. Thomas (Environmental Monitoring and Assessment, 2012)